Participatory analysis of heterogeneity, an approach to consolidate collaborative initiatives at community level - Pokorny, B.; Cayres, G.; Nunes, W. (2003)
Insufficient attention had been given to the development of effective and practicable methodologies to actively involve intra-community groups in constructive discussions about their own heterogeneity and its implications for collaborative action. An approach to participatory analysis of group heterogeneity was tested in three communities in the Eastern Amazon, using four steps: 1. identification of criteria for heterogeneity, 2. definition and characterization of stakeholder types within the community, 3. identification of difficulties, contributions and expectations related to each type, and 4. discussion of findings. The study revealed that the participants of collaboratively working groups at community level are very diverse in their individual characteristics, interests and values. By defining criteria of heterogeneity, developing a typology and using a symbolic language, the groups were enabled to define issues critical to their group and ensure their interest, understanding and acceptance of the aspects discussed. The smallest unit in the typology was in all cases a group member and their related family. Emotional parameters play a key role in people's perceptions of heterogeneity. The proposed approach can be adapted in many ways to facilitate learning about heterogeneity, motivation and the interests of local stakeholders.